MACRO Cooper - Cadieux, Owyn (Northridge Review, 2025)
Digital forensics specialist Damian travels to a lithium mine on a remote asteroid near Jupiter. Titus (owner of one of the most expensive spaceships on the market) and his employee Victoria have commissioned him to investigate their heavy mining equipment for potential malfunctioning. Their findings suddenly become lethal.